Real-time framework for image dehazing based on linear transmission and constant-time airlight estimation - Alajarmeh A.; Salam R.A.; Abdulrahim K.; Marhusin M.F.; Zaidan A.A.; Zaidan B.B. (Elsevier Inc., 2024)
Indexed by WOS/SCOPUS/ERA